Vinyl alcohol block copolymer and method for producing the same
A vinyl alcohol block copolymer with controlled free radical polymerization using an organic cobalt complex addresses the balance of water solubility and mechanical strength in PVA resins, providing stable and strong films.
Patent Information
- Application Number
- CN202080055195.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-28
- Filing Date
- 2020-06-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-06-25
AI Technical Summary
Existing polyvinyl alcohol (PVA) resins face challenges in achieving a balance between water solubility, mechanical strength, and stability in aqueous solutions due to high saponification degrees leading to low crystallinity and insufficient film properties, as well as issues with pH sensitivity and poor solution stability in block copolymers.
A vinyl alcohol block copolymer composed of a vinyl alcohol polymer block and a copolymer block containing vinyl alcohol and acrylic acid monomer units, produced through controlled free radical polymerization using an organic cobalt complex, with specific molecular weight and monomer content ratios, ensuring excellent water solubility and mechanical strength.
The vinyl alcohol block copolymer achieves a balance between high water solubility, stability against pH fluctuations, and mechanical strength, with a narrow molecular weight distribution and controlled polymerization process.
Smart Images

Figure BDA0003493977000000341 
Figure BDA0003493977000000351 
Figure BDA0003493977000000361
Abstract
Description
Technical Field
[0001] The present invention relates to a vinyl alcohol block copolymer which has excellent handleability in an aqueous solution state and can form a film having excellent mechanical strength, and a method for producing the same. Background Art
[0002] Polyvinyl alcohol (hereinafter sometimes referred to as PVA) resin is a crystalline water-soluble polymer material. It has been widely used as an emulsifier, suspending agent, surfactant, fiber processing agent, various adhesives, paper processing agent, adhesive, film, etc., by utilizing its excellent water solubility and film properties (strength, oil resistance, film forming property, oxygen barrier property, etc.). In the past, PVA with different saponification degrees and polymerization degrees was used according to the application. In addition, various modified PVAs with special functions given by introducing functional groups into PVA have been proposed.
[0003] However, since PVA is a crystalline polymer, if the saponification degree is too high, the solubility in water decreases. In this regard, methods are known to reduce the saponification degree in order to ensure water solubility, and methods are known to reduce crystallinity by random copolymerization of vinyl ester and other monomers. However, it is known that when the PVA obtained by such a method is formed into a film, the crystallinity of the film after drying is low, so the performance such as mechanical strength, barrier property, water resistance, etc. is insufficient.
[0004] As a countermeasure to prevent the performance degradation of such films, a method of introducing acrylic units into PVA by random copolymerization to improve water resistance by forming ionic crosslinks has been proposed (Patent Document 1). However, the crystallinity of the PVA obtained by this method is low, so the water resistance and film strength of the obtained film are still insufficient.
[0005] As a method for achieving both the water solubility of PVA and the physical properties of the film, a method of using a block copolymer of a PVA block and a hydrophilic block can be considered.
[0006] Patent document 2 proposes a block copolymer, which is a block copolymer formed by connecting a PVA block with a block formed by copolymerizing a hydrophilic monomer and a hydrophobic monomer with a hydrophobic joint. However, the block polymer has a hydrophobic part, so the water solubility improvement effect is worrying. In addition, in the invention recorded in patent document 2, the terminal of polyvinyl ester is halogenated by chain transfer reaction to form the starting point of block copolymerization, but the chain transfer reaction has the disadvantage of not being able to take into account high molecular weight and high efficiency halogenation. Specifically, if you want to improve the halogenation efficiency, you will promote chain transfer and can not improve the molecular weight of the PVA block, so you can't get sufficient film properties.
[0007] A complete block copolymer of a PVA block and a polyacrylic acid block is described in Non-Patent Document 1. However, the polyacrylic acid block has a high pH sensitivity and therefore may gel in an alkaline aqueous solution and cannot be handled as a solution, and may have poor solution stability, which greatly limits the method of use.
[0008] Non-patent document 2 describes a block copolymer of a vinyl alcohol-acrylate copolymer block and a PVA block obtained by saponifying a block copolymer of a vinyl acetate-acrylate copolymer block and a polyvinyl acetate block in a dehydrating solvent. In the block copolymer described in non-patent document 2, the proportion of the vinyl alcohol-acrylate copolymer block to the PVA block is large, and there is a concern that the film properties derived from PVA cannot be expected.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Laid-Open No. 09-278827
[0012] Patent Document 2: Japanese Patent Application Publication No. 2010-209336
[0013] Non-patent literature
[0014] Non-patent document 1: Highly Stretchable Free-Standing Poly(acrylic acid)-block-poly(vinyl alcohol)Films Obtained from Cobalt-Mediated RadicalPolymerization, Macromolecules, 2017, vol.50, p6054-6063
[0015] Non-patent document 2: Mn2(CO)10-Induced Controlled / Living RadicalCopolymerization of Vinyl Acetate and Methyl Acrylate: Spontaneous Formation of Block Copolymers Consisting of Gradient and Homopolymer Segments, Journal of Polymer Science: Part A: Polymer Chemistry, 2009, vol.47, p1343-1353 Summary of the invention
[0016] Problems to be solved by the invention
[0017] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a vinyl alcohol block copolymer having excellent water solubility, aqueous solution stability and strength, and a method for producing the same.
[0018] Methods used to solve problems
[0019] The above problems can be solved by providing the following vinyl alcohol block copolymer: a vinyl alcohol block copolymer, which is composed of a vinyl alcohol polymer block (Bb) and a copolymer block (Bc) containing a vinyl alcohol monomer unit and an acrylic acid monomer unit, wherein the content (Z) of the acrylic acid monomer unit relative to the total monomer units is 0.05 to 20.0 mol%, the saponification degree is 80 to 99.99 mol%, and the number average molecular weight (Mn) of the block copolymer is a ) is 20000~440000, and the molecular weight distribution (Mw a / Mn a ) is 1.05 to 1.95, and the number average degree of polymerization (DP b ) relative to the number average degree of polymerization (DP a ) ratio (DP b / DP a ) is 0.010~0.999.
[0020] In this case, it is preferred that the number average degree of polymerization (DP b ) is 450 to 5000. It is also preferred that the content (R) of the acrylic acid monomer units in the copolymer block (Bc) is 0.1 to 50.0 mol % relative to all monomer units.
[0021] It is also preferred that the content (Z) [mol %] of the acrylic monomer unit and the crystalline melting temperature (Q) [° C.] of the polymer obtained by re-saponifying the block copolymer to a saponification degree of 99 mol % or more satisfy the following formula (1).
[0022] 2Z+Q≥225 (1)
[0023] The molar ratio (V) of lactone rings to the total of acrylic acid monomer units and lactone rings in the polymer obtained by heat-treating the block copolymer in an acidic aqueous solution and then drying [lactone rings / total of acrylic acid monomer units and lactone rings] is preferably 0.70 or more.
[0024] The above problems can also be solved by providing a method for producing the block copolymer, which comprises: a polymerization step, wherein in the presence of a free radical initiator and an organic cobalt complex, vinyl ester is polymerized and vinyl ester and acrylic ester are copolymerized by controlled free radical polymerization to obtain a vinyl ester block copolymer consisting of a vinyl ester polymer block (B-b1) and a copolymer block (B-c1) containing a vinyl ester monomer unit and an acrylic ester monomer unit; and a saponification step, wherein the vinyl ester block copolymer obtained in the above polymerization step is saponified to obtain a vinyl alcohol block copolymer consisting of a vinyl alcohol polymer block (Bb) and a copolymer block (Bc) containing a vinyl alcohol monomer unit and an acrylic acid monomer unit. In this case, the acrylic ester is preferably methyl acrylate.
[0025] Effects of the Invention
[0026] The vinyl alcohol block copolymer of the present invention has a good balance between excellent water solubility derived from the copolymer block (Bc) and no thickening and gelling due to pH fluctuation, and high mechanical strength derived from the vinyl alcohol polymer block (Bb). According to the production method of the present invention, such a vinyl alcohol block copolymer can be produced. DETAILED DESCRIPTION
[0027] The vinyl alcohol block copolymer of the present invention is composed of a vinyl alcohol polymer block (Bb) and a copolymer block (Bc) containing a vinyl alcohol monomer unit and an acrylic acid monomer unit, wherein the content (Z) of the acrylic acid monomer unit relative to the total monomer units is 0.05 to 20.0 mol%, the degree of saponification is 80 to 99.99 mol%, and the number average molecular weight (Mn) of the block copolymer is a ) is 20000~440000, and the molecular weight distribution (Mw a / Mn a ) is 1.05 to 1.95, and the number average degree of polymerization (DP b ) relative to the number average degree of polymerization (DP a ) ratio (DP b / DP a ) is 0.010~0.999.
[0028] The vinyl alcohol block copolymer of the present invention has excellent water solubility, does not thicken or gel due to pH fluctuation, and exhibits high mechanical strength while maintaining an excellent balance. It is believed that the water solubility and stability against pH fluctuation are due to the copolymer block (Bc) containing vinyl alcohol monomer units and acrylic acid monomer units functioning as hydrophilic monomer units, and the mechanical strength is due to the vinyl alcohol polymer block (Bb).
[0029] The preferred method for producing the vinyl alcohol block copolymer of the present invention comprises: a polymerization step, in which vinyl ester is polymerized and vinyl ester and acrylic ester are copolymerized by controlled free radical polymerization in the presence of a free radical initiator and an organic cobalt complex to obtain a vinyl ester block copolymer consisting of a vinyl ester polymer block (B-b1) and a copolymer block (B-c1) containing a vinyl ester monomer unit and an acrylic ester monomer unit; and a saponification step, in which the vinyl ester block copolymer obtained in the above polymerization step is saponified to obtain a vinyl alcohol block copolymer consisting of a vinyl alcohol polymer block (Bb) and a copolymer block (Bc) containing a vinyl alcohol monomer unit and an acrylic ester monomer unit. The production method is described in detail below.
[0030] First, the polymerization process is described. In the polymerization process, in the presence of a free radical initiator and an organic cobalt complex, vinyl ester polymerization and copolymerization of vinyl ester and acrylic ester are carried out by controlled free radical polymerization. The vinyl ester polymer block (B-b1) is obtained by polymerizing the vinyl ester, and the copolymer block (B-c1) containing vinyl ester monomer units and acrylic ester monomer units is obtained by randomly copolymerizing the vinyl ester and acrylic ester.
[0031] The controlled radical polymerization used in the production method of the present invention refers to a polymerization reaction in which the propagating radical end (active species) reacts in a state of equilibrium with the covalently bonded species (dormant species) to which the control agent is bonded. In the production method of the present invention, an organic cobalt complex is preferably used as the control agent.
[0032] As the polymerization method, known methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization can be listed. Among them, bulk polymerization in which polymerization is performed without a solvent or solution polymerization in various organic solvents is generally used. In order to obtain a polymer with a narrow molecular weight distribution, bulk polymerization without using a solvent or a dispersion medium that may cause side reactions such as chain transfer is preferred. On the other hand, from the perspective of adjusting the viscosity of the reaction solution and controlling the polymerization rate, solution polymerization is sometimes preferred. As for the organic solvent used as a solvent during solution polymerization, esters such as methyl acetate and ethyl acetate; aromatic hydrocarbons such as benzene and toluene; lower alcohols such as methanol and ethanol; etc. Among these, esters and aromatic hydrocarbons are preferably used to prevent chain transfer. The amount of solvent used can be determined based on the number average molecular weight of the target block copolymer and in consideration of the viscosity of the reaction solution. For example, it can be selected from a range of mass ratios (solvent / monomer) of 0.01 to 10. The mass ratio (solvent / monomer) is preferably greater than 0.1 and preferably less than 5.
[0033] As the free radical initiator used in the polymerization process, the known azo initiator, peroxide initiator, redox initiator, etc. can be appropriately selected. As the azo initiator, 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), etc. can be listed, and as the peroxide initiator, percarbonate compounds such as diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, and diethoxyethyl peroxydicarbonate can be listed; perester compounds such as tert-butyl peroxyneodecanoate, isopropyl peroxyneodecanoate, and tert-butyl peroxyneodecanoate; acetylcyclohexylsulfonyl peroxide, diisobutyryl peroxide; 2,4,4-trimethylpentyl-2-peroxyphenoxyacetate, etc. can be listed. In addition, potassium persulfate, ammonium persulfate, hydrogen peroxide, etc. can be combined with the above-mentioned initiators to serve as an initiator. In addition, as redox initiators, there can be mentioned initiators composed of the above-mentioned peroxides and reducing agents such as sodium bisulfite, sodium bicarbonate, tartaric acid, L-ascorbic acid, and Rongalite. The amount of the initiator used varies depending on the polymerization catalyst and cannot be generalized. It can be arbitrarily selected according to the polymerization rate.
[0034] The organic cobalt complex used as a control agent in the polymerization step is a complex containing a divalent cobalt atom and an organic ligand. Preferred organic cobalt complexes include, for example, cobalt (II) acetylacetonate [Co(acac)2], porphyrin cobalt (II) complexes, etc. Among them, cobalt (II) acetylacetonate is preferred from the viewpoint of manufacturing cost.
[0035] In the controlled radical polymerization used in the present invention, first, the free radicals generated by the decomposition of the free radical initiator are bonded to a small number of monomers, and the free radicals at the growing ends of the generated short-chain polymers are bonded to the organic cobalt (II) complex to generate dormant species formed by covalent bonding of the organic cobalt (III) complex and the polymer ends. In a certain period after the start of the reaction, only short-chain polymers are generated and converted into dormant species, and substantially no high degree of polymerization occurs. This period is called the induction period. After the organic cobalt (II) complex is consumed, the growth period in which a high degree of polymerization occurs begins, and the molecular weight of almost all molecular chains in the reaction system increases in the same manner in proportion to the polymerization time. In this way, a vinyl ester block copolymer with a narrow molecular weight distribution can be obtained. The time required for the polymerization process of the monomers is the sum of the induction period and the growth period, which is usually 3 to 50 hours.
[0036] As described above, in the controlled radical polymerization of the present invention, theoretically, one polymer chain is generated by one molecule of the added organic cobalt complex. Therefore, the amount of the organic cobalt complex added to the reaction solution can be determined in consideration of the target number average molecular weight and polymerization rate. Generally, it is preferred to use 0.001 to 1 mole of the organic cobalt complex relative to 100 moles of the monomer.
[0037] When the molar number of the free radicals produced is less than the molar number of the organic cobalt complex, the polymerization reaction is carried out only by the mechanism of thermal dissociation of the cobalt complex from the dormant species, and therefore, according to the reaction temperature, the polymerization rate becomes extremely small. Therefore, if it is considered that the free radical initiator produces two free radicals, it is necessary to make the molar number of the free radical initiator used be an amount exceeding 1 / 2 times the molar number of the organic cobalt complex. Generally speaking, the amount of active free radicals supplied by the initiator depends on the initiator efficiency, therefore, there is actually an initiator that is not used for the formation of dormant species and is inactivated. Therefore, the molar number of the free radical initiator used is preferably more than 1 times the molar number of the organic cobalt complex, more preferably more than 1.5 times. On the other hand, when the molar number of the free radicals produced is too much compared with the molar number of the organic cobalt complex, the ratio of uncontrolled free radical polymerization increases, and therefore, the molecular weight distribution broadens. The molar number of the free radical initiator used is preferably less than 10 times the molar number of the organic cobalt complex, more preferably less than 6 times.
[0038] Examples of the vinyl ester used in the production method of the present invention include vinyl formate, vinyl acetate, vinyl trifluoroacetate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, and vinyl versatate. From an economical point of view, vinyl acetate is preferably used.
[0039] Examples of the acrylic acid ester used in the production method of the present invention include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, dodecyl acrylate, and octadecyl acrylate. Among them, methyl acrylate is preferred.
[0040] In addition, the vinyl alcohol block copolymer of the present invention may contain monomer units derived from ethylenically unsaturated monomers copolymerizable with vinyl esters and acrylic esters within a range that does not impair the effects of the present invention. Examples of the ethylenically unsaturated monomers include olefins such as ethylene, propylene, 1-butene, and isobutylene; acrylamides such as acrylamide, N-alkyl (carbon number 1 to 18) acrylamide, N,N-dimethylacrylamide, 2-acrylamide propanesulfonic acid or its salt, acrylamidopropyl dimethylamine or its acid salt or its quaternary salt; methacrylamide, N-alkyl (carbon number 1 to 18) methacrylamide, N,N-dimethyl methacrylamide, 2-methacrylamide propanesulfonic acid or its salt, methacrylamidopropyl dimethylamine or its acid salt or its quaternary salt; N-vinylpyrrole N-vinyl amides such as alkanone, N-vinyl formamide, and N-vinylacetamide; vinyl cyanides such as acrylonitrile and methacrylonitrile; vinyl ethers such as alkyl (carbon number 1 to 18) vinyl ethers, hydroxyalkyl vinyl ethers, and alkoxyalkyl vinyl ethers; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride, and vinyl bromide; vinyl silanes such as trimethoxyvinylsilane; allyl compounds such as allyl acetate, allyl chloride, allyl alcohol, and dimethylallyl alcohol; trimethyl-(3-acrylamide-3-dimethylpropyl)-ammonium chloride, acrylamide-2-methylpropanesulfonic acid, etc.
[0041] The content of monomer units other than vinyl alcohol monomer units and acrylic acid monomer units in blocks (Bb) and (Bc) constituting the above-mentioned vinyl alcohol block copolymer is preferably 10 mol% or less, more preferably 3 mol% or less, further preferably 1 mol% or less, and particularly preferably substantially free of them, relative to all monomer units in each block.
[0042] As long as it is a method that generates dormant species and can control the high degree of polymerization of the polymer, the mixing method of the free radical initiator, the organic cobalt complex and the monomer is not particularly limited. For example, the following methods can be cited: after mixing the free radical initiator and the organic cobalt complex, the resulting mixture is mixed with the monomer; the method of mixing the free radical initiator, the organic cobalt complex and the monomer at one time; after mixing the organic cobalt complex with the monomer, the resulting mixture is mixed with the free radical initiator, etc. In addition, the free radical initiator, the organic cobalt complex and the monomer can also be mixed in batches. For example, the following methods can be cited: mixing the free radical initiator and the organic cobalt complex with a part of the monomer, thereby generating a dormant species formed by covalently bonding the organic cobalt (III) complex to the polymer end of the short chain, and then mixing the dormant species with the remainder of the monomer to achieve a high degree of polymerization. It should be noted that the dormant species can also be separated as a macromolecular initiator and mixed with the remainder of the monomer to achieve a high degree of polymerization.
[0043] In the above-mentioned polymerization process, either the polymerization of vinyl ester or the copolymerization of vinyl ester and acrylate can be carried out first. When the polymerization of vinyl ester is carried out first, vinyl ester, other monomers other than vinyl ester and acrylate as required, free radical initiator and organic cobalt complex are mixed by the above-mentioned method, thereby starting the polymerization of vinyl ester. In the polymerization of vinyl ester, it is preferred not to use acrylate. Then, when the number average polymerization degree of the vinyl ester polymer reaches the target value, acrylate is added to the reaction solution to start the copolymerization of the remaining vinyl ester and acrylate. At this time, the additional vinyl ester, other monomers other than acrylate and vinyl ester can be added together with acrylate as needed. The number average polymerization degree of the polymer can be confirmed by GPC (gel permeation chromatography) method, specifically, the method described in the embodiments described later can be adopted.
[0044] When the polymerization of vinyl ester is first performed, in the case of obtaining a binary vinyl ester block copolymer having one vinyl ester polymer block (B-b1) and one copolymer block (B-c1) containing a vinyl ester monomer unit and an acrylate monomer unit, it is preferred to terminate the reaction before the disappearance of the acrylate. On the other hand, in the case of obtaining a polyvalent vinyl ester block copolymer having a ternary or higher structure, it is preferred to continue the polymerization to form the vinyl ester polymer block (B-b1) even after the acrylate disappears. According to this method, a ternary vinyl ester block copolymer such as block (B-b1)-block (B-c1)-block (B-b1) can be obtained. In the present invention, the portion obtained by polymerizing the remaining vinyl ester in a state where the molar ratio of the acrylate in the reaction solution to the vinyl ester (acrylate / vinyl ester) is less than 0.00001 is used as the vinyl ester polymer block (B-b1). The moment when the molar ratio (acrylate / vinyl ester) reaches 0.00001 can be determined by the method described in the examples. When the number average molecular weight of the vinyl ester block copolymer reaches the target value, the reaction is terminated, or when a tetravalent or higher polyvalent vinyl ester block copolymer is to be obtained, acrylic acid ester is added again to the reaction solution to continue polymerization.
[0045] When copolymerization of vinyl ester and acrylate is first performed in the above-mentioned polymerization step, vinyl ester and acrylate, other monomers other than vinyl ester and acrylate as required, a free radical initiator and an organic cobalt complex are mixed by the above-mentioned method to start copolymerization of vinyl ester and acrylate, and then each block is formed in sequence.
[0046] The polymerization temperature is preferably, for example, 0°C to 80°C. When the polymerization temperature is lower than 0°C, the polymerization rate tends to be insufficient and the productivity tends to decrease. From this point of view, the polymerization temperature is more preferably 10°C or higher, and more preferably 20°C or higher. On the other hand, when the polymerization temperature exceeds 80°C, the molecular weight distribution of the obtained vinyl alcohol block copolymer tends to become broad. From this point of view, the polymerization temperature is more preferably 65°C or lower, and more preferably 50°C or lower.
[0047] In the above-mentioned polymerization process, it is preferred to perform a termination process of terminating the polymerization reaction by adding a polymerization terminator when the number average degree of polymerization and the polymerization rate of the vinyl ester block copolymer reach the target values. Examples of the polymerization terminator include: 1,1-diphenylethylene; styrene compounds such as styrene, α-methylstyrene and 4-tert-butylstyrene; hydroxy aromatic compounds such as p-methoxyphenol, hydroquinone, cresol, tert-butylcatechol, and p-nitrophenol; quinone compounds such as benzoquinone and naphthoquinone; conjugated carboxylic acids such as muconic acid and sorbic acid; sulfides such as phenothiazine, distearyl thiodipropionate, and dilauryl thiodipropionate; aromatic amines such as p-phenylenediamine and N-nitrodiphenylamine; nitrogen oxides such as 2,2,6,6-tetramethylpiperidine 1-oxide and 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxide; transition metal salts such as copper acetate, copper dithiocarbamate, and manganese acetate, etc. Among them, 1,1-diphenylethylene, sorbic acid and benzoquinone are preferred, and 1,1-diphenylethylene is more preferred.
[0048] The molar number of the added polymerization terminator is preferably 1 to 100 mol relative to 1 mol of the added organic cobalt complex. When the molar number of the above-mentioned polymerization terminator is too small, the free radicals at the polymer terminal cannot be fully captured, and the color tone of the obtained vinyl alcohol block copolymer may be deteriorated. On the other hand, when the molar number of the above-mentioned polymerization terminator is too large, the production cost may increase.
[0049] The temperature of the reaction solution in the termination step may be any temperature at which the polymerization terminator can react with the radical at the terminal of the vinyl ester block copolymer, and is preferably 0 to 80° C. The time required for the termination step is usually 10 minutes to 5 hours.
[0050] Preferably, an extraction process is performed before the saponification process, wherein the extraction process is a process of contacting the obtained vinyl ester block copolymer solution with an aqueous solution containing a water-soluble ligand and extracting and removing the cobalt complex from the above-mentioned vinyl ester block copolymer solution. In this way, by performing a saponification process after removing the cobalt complex contained in the vinyl ester block copolymer solution in advance, a vinyl alcohol block copolymer with good hue and difficult gelation can be obtained. Specifically, the following operation can be performed: the above-mentioned aqueous solution and the above-mentioned vinyl ester block copolymer solution, which are insoluble in each other, are stirred vigorously in a manner that increases the area of the interface between the two, and then left to stand, separated into an oil layer and a water layer, and the water layer is removed. This operation can be repeated many times.
[0051] The water-soluble ligand used in the extraction process is preferably an acid having a pKa of 0 to 12 at 25°C. When a strong acid having a pKa of less than 0 is used, it is difficult to efficiently extract the cobalt complex, and the pKa is preferably greater than 2. In addition, when a weak acid having a pKa of greater than 12 is used, it is also difficult to efficiently extract the cobalt complex, and the pKa is preferably less than 7. When the above-mentioned acid is a polyacid, the first dissociation constant (pKa1) needs to be within the above-mentioned range. The acid having a pKa of 0 to 12 is preferably a carboxylic acid or phosphoric acid (pKa1 is 2.1), and more preferably a carboxylic acid. Among them, acetic acid (pKa is 4.76) is particularly preferred.
[0052] The pH of the aqueous solution containing the water-soluble ligand is preferably 0 to 5. The pH is more preferably 1 or more, and even more preferably 1.5 or more. The pH is more preferably 4 or less, and even more preferably 3 or less.
[0053] In the saponification step, the vinyl ester block copolymer obtained in the polymerization step is saponified to obtain a vinyl alcohol block copolymer composed of a vinyl alcohol polymer block (Bb) and a copolymer block (Bc) containing a vinyl alcohol monomer unit and an acrylic acid monomer unit.
[0054] In the saponification step, the vinyl ester block copolymer produced by the above method may be dissolved in alcohol and saponified to obtain the vinyl alcohol block copolymer. In this case, the vinyl ester monomer units in the vinyl ester block copolymer may be converted into vinyl alcohol monomer units.
[0055] In addition, by adjusting the saponification conditions, the acrylate monomer units can be converted into acrylic acid monomer units. From the viewpoint of improving the mechanical properties of the vinyl alcohol block copolymer, the molar ratio of the acrylic acid monomer units to the total of the acrylate monomer units and the acrylic acid monomer units in the vinyl alcohol block copolymer [acrylic acid monomer units / the total of the acrylate monomer units and the acrylic acid monomer units] is preferably 0.5 or more, more preferably 1.0.
[0056] Depending on the saponification conditions, the acrylic acid ester monomer unit or acrylic acid monomer unit may form a lactone ring with the adjacent vinyl alcohol monomer unit.
[0057] As the alcohol used in the saponification reaction, lower alcohols such as methanol and ethanol can be mentioned, and methanol is particularly preferably used. In addition, the above-mentioned alcohol may be a hydrous alcohol or a dehydrated alcohol. The alcohol used in the saponification reaction may contain esters such as acetone, methyl acetate or ethyl acetate, and solvents such as toluene. As the catalyst used in the saponification reaction, for example: alkali metal hydroxides such as potassium hydroxide and sodium hydroxide; base catalysts such as sodium methoxide; acid catalysts such as inorganic acids. Regarding the temperature of the saponification reaction, for example, the range of 20 to 70°C is suitable. In the case where a gel-like product is precipitated as the saponification reaction proceeds, the product is crushed at this time, washed and dried, thereby obtaining the vinyl alcohol block copolymer of the present invention.
[0058] The vinyl alcohol block copolymer of the present invention thus obtained is composed of a vinyl alcohol polymer block (Bb) and a copolymer block (Bc) containing a vinyl alcohol monomer unit and an acrylic monomer unit. The vinyl alcohol block copolymer can be a binary block copolymer consisting of 1 vinyl alcohol polymer block (Bb) and 1 copolymer block (Bc), or a ternary block copolymer consisting of 1 vinyl alcohol polymer block (Bb) and 2 copolymer blocks (Bc), or a ternary block copolymer consisting of 2 vinyl alcohol polymer blocks (Bb) and 1 copolymer block (Bc), or a multi-block copolymer consisting of a total of more than 4 vinyl alcohol polymer blocks (Bb) and copolymer blocks (Bc). Wherein, the above-mentioned vinyl alcohol block copolymer is preferably a binary block copolymer or a ternary block copolymer, more preferably a binary block copolymer. The bonding mode of the vinyl alcohol polymer block (Bb) and the copolymer block (Bc) is preferably linear.
[0059] The saponification degree of the vinyl alcohol block copolymer of the present invention is 80 to 99.99 mol%. In the present invention, the saponification degree refers to: the ratio (mol%) of the total molar number of vinyl alcohol monomer units and units derived from vinyl alcohol monomers that form lactone rings relative to the total molar number of vinyl ester monomer units, vinyl alcohol monomer units, and units derived from vinyl alcohol monomers that form lactone rings in the vinyl alcohol block copolymer. When the saponification degree is lower than 80 mol%, the crystallinity of the vinyl alcohol polymer block (Bb) decreases significantly, and the physical properties such as mechanical strength and barrier properties of the formed coating decrease. The saponification degree is preferably 85 mol% or more, more preferably 90 mol% or more. On the other hand, when the saponification degree exceeds 99.99 mol%, there is a tendency that the manufacture of the vinyl alcohol block copolymer becomes difficult and the moldability is also poor. The saponification degree is preferably 99.95 mol% or less. The saponification degree can be measured by the degree of saponification of the vinyl alcohol block copolymer.1 It can be determined by H-NMR measurement, and specifically, the method described in Examples can be used.
[0060] The content (Z) of the acrylic monomer unit relative to all monomer units in the vinyl alcohol block copolymer of the present invention is 0.05 to 20.0 mol%. In the present invention, the acrylic monomer unit refers to an acrylic monomer unit, an acrylate monomer unit and a lactone ring, and the total content of these monomer units needs to be within the above range. The vinyl alcohol block copolymer of the present invention contains at least one acrylic monomer unit selected from the group consisting of an acrylic monomer unit, an acrylate monomer unit and a lactone ring. When the content (Z) is less than 0.05 mol%, the water solubility of the vinyl alcohol block copolymer may decrease. The content (Z) is preferably 0.2 mol% or more, more preferably 0.5 mol% or more, and further preferably 3.0 mol% or more. On the other hand, when the content (Z) exceeds 20.0 mol%, the mechanical strength of the obtained film decreases. The content (Z) is preferably 18.0 mol% or less, more preferably 14.0 mol% or less.
[0061] The content of the vinyl alcohol monomer units in the vinyl alcohol polymer block (Bb) relative to all monomer units is preferably 90 mol% or more, more preferably 97 mol% or more, and further preferably 99 mol% or more. In the present invention, the vinyl alcohol monomer units refer to vinyl ester monomer units and vinyl alcohol monomer units, and the content of the vinyl alcohol monomer units refers to the total content of the vinyl ester monomer units and the vinyl alcohol monomer units.
[0062] The content of the vinyl alcohol unit in the vinyl alcohol polymer block (Bb) relative to all monomer units is preferably 95 mol% or more, more preferably 98 mol% or more, and even more preferably 99 mol% or more.
[0063] The content of the acrylic acid-based monomer units in the vinyl alcohol-based polymer block (Bb) is usually less than 0.1 mol % based on all monomer units.
[0064] The content (R) of the acrylic monomer unit relative to all monomer units in the copolymer block (Bc) containing vinyl alcohol monomer units and acrylic monomer units is preferably 0.1 to 50.0 mol%. When the content (R) is less than 0.1 mol%, the water solubility of the vinyl alcohol block copolymer is likely to decrease. The content (R) is more preferably 0.5 mol% or more, more preferably 2 mol% or more, and particularly preferably 5 mol% or more. On the other hand, when the content (R) exceeds 50.0 mol%, the stability of the above-mentioned vinyl alcohol block copolymer relative to the pH change of the aqueous solution is likely to decrease, and the swelling property of the film obtained may be excessively increased and the mechanical strength may decrease. The content (R) is more preferably 40.0 mol% or less, and more preferably 30.0 mol% or less.
[0065] The number average molecular weight (Mn a ) is 20000 to 440000. By using an organic cobalt complex as a control agent, a narrow molecular weight distribution and a number average molecular weight (Mn a ) is a vinyl alcohol block copolymer with high mechanical strength. From the perspective of obtaining a film with high mechanical strength, the number average molecular weight (Mn a ) is preferably 30,000 or more, more preferably 40,000 or more, particularly preferably 50,000 or more, and most preferably 60,000 or more. a ) is too high, the viscosity of the solution becomes excessively high and becomes difficult to handle, and the dissolution rate decreases. Therefore, the number average molecular weight (Mn a ) is preferably 220,000 or less. Number average molecular weight (Mn a ) and molecular weight distribution (Mw a / Mn a ) is a value obtained by measuring the vinyl alcohol block copolymer using polymethyl methacrylate as a standard substance and a hexafluoroisopropanol (HFIP) column by GPC method. The measurement method is as described in the Examples.
[0066] The molecular weight distribution (Mw a / Mn a ) is 1.05 to 1.95. By using controlled radical polymerization to carry out polymerization, a vinyl alcohol block copolymer with a narrow molecular weight distribution can be obtained. Molecular weight distribution (Mw a / Mn a ) is preferably 1.80 or less, more preferably 1.65 or less, and further preferably 1.55 or less. Molecular weight distribution (Mw a / Mn a) is within the above range, the crystallinity of the obtained vinyl alcohol block copolymer is further improved, and the mechanical strength and gas barrier properties of the obtained film are improved.
[0067] The number average degree of polymerization (DP) of the vinyl alcohol polymer block (Bb) is b ) relative to the number average degree of polymerization (DP a ) ratio (DP b / DP a ) needs to be 0.010 to 0.999. b / DP a When DP is less than 0.010, the mechanical strength and gas barrier properties of the obtained film decrease. b / DP a ) is preferably 0.05 or more, more preferably 0.1 or more, and still more preferably 0.3 or more. b / DP a When ) exceeds 0.999, the water solubility of the vinyl alcohol block copolymer may decrease. b / DP a ) is preferably 0.995 or less, more preferably 0.99 or less, and further preferably 0.8 or less.
[0068] The number average degree of polymerization (DP a ) can be measured by GPC of the above vinyl ester block copolymer after polymerization termination and 1 The molecular weight of the vinyl ester block copolymer obtained after the H-NMR measurement and the content of each monomer unit can be used for calculation. Specifically, the method described in the examples described later can be used.
[0069] The number average degree of polymerization (DP) of the vinyl alcohol polymer block (Bb) is b ) can be carried out by GPC measurement of the polymer obtained by sampling the reaction solution during polymerization, 1 The molecular weight can be calculated from the number average molecular weight of the polymer obtained after the H-NMR measurement and the content of each monomer unit. Specifically, the method described in the examples described later can be used.
[0070] The number average degree of polymerization (DP) of the vinyl alcohol polymer block (Bb) is b ) is preferably 450 to 5000. When the vinyl alcohol block copolymer contains two or more vinyl alcohol polymer blocks (Bb), the sum of the average polymerization degrees of the vinyl alcohol polymer blocks (Bb) is taken as the number average polymerization degree (DP b ). Number average degree of polymerization (DP b) is less than 450, the mechanical strength of the obtained film may decrease. b ) is preferably 600 or more, more preferably 800 or more, and further preferably 1200 or more. On the other hand, the number average degree of polymerization (DP b ) exceeds 5000, the water solubility may decrease. b ) is more preferably 4000 or less, and further preferably 3000 or less.
[0071] The molar ratio (V) [the total of lactone ring / acrylic acid monomer unit and lactone ring] of the lactone ring in the polymer obtained by heating the above-mentioned vinyl alcohol block copolymer in an acidic aqueous solution and drying is preferably 0.70 or more. By heating the above-mentioned vinyl alcohol block copolymer in an acidic aqueous solution, the acrylate monomer unit is converted into an acrylic acid monomer unit. In addition, by the above-mentioned treatment, the acrylic acid monomer unit and the acrylic acid ester monomer unit adjacent to the vinyl alcohol monomer unit and capable of forming a lactone ring with the vinyl alcohol monomer unit are converted into a lactone ring. On the other hand, in the case where the acrylic acid ester monomer unit and the acrylic acid monomer unit are continuous, the lactone ring is not formed even if the above-mentioned treatment is performed, and it remains in the form of an acrylic acid monomer unit. Therefore, when the proportion of the part where the vinyl alcohol monomer unit and the acrylic acid monomer unit or the acrylic acid ester monomer unit are alternately arranged is large, that is, the proportion of the part where the acrylic acid ester monomer unit and the acrylic acid monomer unit are continuous is small, the molar ratio (V) [the total of lactone ring / acrylic acid monomer unit and lactone ring] becomes high. That is, the molar ratio (V) [the total of lactone ring / acrylic acid monomer unit and lactone ring] is an index of the randomness of the copolymer block (Bc) containing vinyl alcohol monomer units and acrylic acid monomer units. By making the molar ratio (V) [the total of lactone ring / acrylic acid monomer unit and lactone ring] greater than 0.70, the stability of the vinyl alcohol block copolymer relative to pH fluctuations is further improved, and even if the pH changes when an aqueous solution is made, gelation and thickening are less likely to occur. The molar ratio (V) [the total of lactone ring / acrylic acid monomer unit and lactone ring] is more preferably greater than 0.80. The conditions for the heating treatment and drying of the above-mentioned vinyl alcohol block copolymer can adopt the conditions described in the embodiments.
[0072] The content (Z) [mol %] of the acrylic acid monomer unit in the above-mentioned vinyl alcohol block copolymer and the crystalline melting temperature (Q) [°C] of the polymer obtained by re-saponifying the above-mentioned vinyl alcohol block copolymer to a saponification degree of 99 mol % or more preferably satisfy the following formula (1), and more preferably satisfy the following formula (2).
[0073] 2Z+Q≥225 (1)
[0074] 2Z+Q≥230 (2)
[0075] The vinyl alcohol block copolymer satisfies the above formula (1), that is, the vinyl alcohol block copolymer having a high content (Z) of acrylic acid monomer units and a high crystalline melting temperature (Q) has an extremely good balance between water solubility, water absorption and mechanical strength of the coating.
[0076] Usually, when making vinyl ester and other monomer monomers random copolymerization, the crystallinity of the obtained vinyl alcohol copolymer is extremely low, and it is difficult to take into account both water solubility and the strength of the formed film. On the other hand, it is believed that in the vinyl alcohol block copolymer of the present invention, the crystallinity of the vinyl alcohol polymer block (Bb) is good, so even when the content of acrylic acid monomer units is large, high film strength can be maintained. Therefore, it is believed that the above-mentioned vinyl alcohol block copolymer can take into account water solubility, water absorption and high film strength. In addition, the above-mentioned vinyl alcohol block copolymer can also form a phase separation structure. In the case where the film obtained using the above-mentioned vinyl alcohol block copolymer has a phase separation structure, the crystallinity of the phase from the vinyl alcohol polymer block (Bb) is good, so high mechanical strength can also be maintained.
[0077] The vinyl alcohol block copolymer is preferably water-soluble. Whether the vinyl alcohol block copolymer is water-soluble is determined by adding the vinyl alcohol block copolymer to ion exchange water in a concentration of 4 mass %, heating and stirring at 100° C., and determining whether the vinyl alcohol block copolymer is completely dissolved within 6 hours after the temperature is raised.
[0078] As the molding method of the vinyl alcohol block copolymer of the present invention, for example, there can be mentioned: a method of molding from a solution form of water or dimethyl sulfoxide, etc.; a method of molding by plasticizing the above vinyl alcohol block copolymer by heating, such as extrusion molding, injection molding, inflation molding, press molding, blow molding, etc. By using these methods, molded products of any shape such as fibers, films, sheets, tubes, bottles, etc. can be obtained.
[0079] Various additives may be added to the vinyl alcohol block copolymer of the present invention within the range that does not impair the effects of the present invention. Examples of additives include fillers, processing stabilizers such as copper compounds, weathering stabilizers, colorants, ultraviolet absorbers, light stabilizers, antioxidants, antistatic agents, flame retardants, plasticizers, other resins such as starch, lubricants, fragrances, defoamers, deodorants, extenders, stripping agents, mold release agents, reinforcing agents, crosslinking agents, mildew inhibitors, preservatives, crystallization rate retarders, and the like.
[0080] The vinyl alcohol block copolymer of the present invention can be used in various applications by utilizing its characteristics, for example, it can be used in surfactants, paper coating agents, paper additives, pigment binders, adhesives, non-woven fabric binders, coatings, fiber processing agents, fiber pastes, dispersion stabilizers, films (optical films, water-soluble films), sheets, bottles, fibers, thickeners, flocculants, soil conditioners, and the like.
[0081] Example
[0082] [Number average molecular weight (Mn) and molecular weight distribution (Mw / Mn)]
[0083] The number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the polymer were measured using a size exclusion high performance liquid chromatography apparatus "HLC-8320GPC" manufactured by Tosoh Corporation. The measurement conditions are as follows.
[0084] Chromatographic columns: Two HFIP columns "GMHHR-H(S)" manufactured by Tosoh Corporation connected in series
[0085] Standard sample: polymethyl methacrylate
[0086] Solvent and mobile phase: sodium trifluoroacetate-HFIP solution (concentration 20 mM)
[0087] Flow rate: 0.2mL / min
[0088] Temperature: 40℃
[0089] Sample solution concentration: 0.1 mass% (filtered with a filter with a pore size of 0.45 μm)
[0090] Injection volume: 10 μL
[0091] Detector: RI
[0092] [Content of Acrylate Monomer Units in Vinyl Ester Block Copolymer (U)]
[0093] The content (U) (mol%) of the acrylic acid ester monomer unit in the vinyl ester block copolymer is determined by the following method. 1 H-NMR measurement. The methine protons (-CH2C H The integrated value of the peak of (OCOCH3)-) (4.8 ppm) was set as T, and the side chain proton (-CH2CH(COOC H3 The integrated value (3.6 ppm) of the peak of )-) was defined as S, and the content (U) (mol %) of the acrylic acid ester monomer unit in the vinyl ester block copolymer was calculated by the following formula.
[0094] (U) (mol%) = (S / 3) / (S / 3 + T) × 100
[0095] [Number average degree of polymerization DP of vinyl alcohol block copolymer a and the number average degree of polymerization DP of the vinyl alcohol polymer block (Bb) b ]
[0096] The number average degree of polymerization DP of the vinyl alcohol polymer block (Bb) in the vinyl alcohol block copolymer is determined as follows: b .
[0097] The vinyl alcohol polymer block (Bb) can be formed by saponifying the vinyl ester polymer block (B-b1) in the vinyl ester block copolymer. b Since there is substantially no change before and after saponification, the number average degree of polymerization determined from the GPC measurement results of the polymer before saponification is taken as the number average degree of polymerization DP of the vinyl alcohol polymer block (Bb). b Similarly, the number average degree of polymerization DP of the vinyl alcohol block copolymer was determined from the GPC measurement results of the polymer after polymerization termination and before saponification. a .
[0098] Here, the vinyl ester polymer block (B-b1) refers to: a block obtained by polymerizing vinyl ester in the absence of the coexistence of acrylic ester; and a block obtained by polymerizing vinyl ester monomers in a state where the molar ratio of acrylic ester to vinyl ester in the reaction solution (acrylic ester / vinyl ester) is less than 0.00001, after obtaining a copolymer block (B-c1) containing vinyl ester monomer units and acrylic ester monomer units by polymerizing vinyl ester in the coexistence of acrylic ester at the beginning of polymerization or during polymerization, and the acrylic ester is consumed before the vinyl ester.
[0099] The boundary between the "vinyl ester polymer block (B-b1)" and the "copolymer block containing vinyl ester monomer units and acrylic ester monomer units (B-c1)" is determined as follows. Sampling is appropriately performed during the polymerization, and the GPC and 1 The number average degree of polymerization (DP) and the content (U) (mol %) of the acrylate monomer at each sampling time were measured by H-NMR. The Mayo-Lewis formula of copolymerization theory and the value of the reactivity ratio (r VAc =0.01, r MA = 30) to find the time when the molar ratio (acrylate / vinyl ester) reaches 0.00001. At this time, the content of the acrylate monomer unit contained in the vinyl ester polymer block formed after the molar ratio (acrylate / vinyl ester) reaches 0.00001 is less than 0.1 mol%.
[0100] The number average degree of polymerization (DP) of the sampled polymers was determined by GPC and 1 The number average molecular weight Mn of the polymer obtained by H-NMR, the content (U) (mol %) of the acrylic acid ester monomer unit, and the molecular weights of the acrylic acid ester monomer unit and the vinyl ester monomer unit (methyl acrylate: 86, vinyl acetate: 86) were determined from the following formulas.
[0101] (DP)=Mn / {(U / 100)×86+[(100-U) / 100]×86}
[0102] =Mn / 86
[0103] Number average degree of polymerization DP of vinyl alcohol block copolymers a The vinyl ester block copolymers after polymerization were analyzed by GPC and 1 When a vinyl ester polymer block is obtained at the beginning of polymerization, the number average degree of polymerization DP of the vinyl alcohol polymer block (Bb) is determined by measuring the polymer sampled just before the addition of the acrylic acid ester. b When a vinyl ester polymer block is obtained by copolymerizing acrylic ester and vinyl ester, the number average degree of polymerization DP of the vinyl alcohol polymer block (Bb) is determined from the difference between the number average degrees of polymerization obtained by measuring the polymer sampled at the time of forming the block boundary and the polymer sampled immediately before adding acrylic ester. b .
[0104] [Content (Z) of acrylic acid monomer units in vinyl alcohol block copolymer (mol%)]
[0105] The vinyl alcohol block copolymer was stirred in a hydrochloric acid aqueous solution of pH 2 at 100°C for 1 hour and then dried at 120°C to convert the acrylic acid monomer unit in the copolymer into an acrylic acid monomer unit or a lactone ring structure (the lactone ring is formed by reacting the acrylic acid monomer unit or the acrylic acid ester monomer unit with the vinyl alcohol monomer unit adjacent thereto). The copolymer was washed with methanol to remove the salt, and then dried under reduced pressure at 90°C for 2 days. The copolymer was then subjected to nuclear magnetic resonance at 40°C and 95°C using a nuclear magnetic resonance apparatus "LAMBDA 500" manufactured by JEOL Ltd. 1 H-NMR measurement. DMSO-d6 was used as a solvent. The content (Z) (mol %) of the acrylic acid-based monomer unit relative to all monomer units of the vinyl alcohol-based block copolymer was calculated as follows.
[0106] The side chain protons (-CH2CH(COO HThe integrated value of the peak of )-) (broad peak detected in the range of 11.0 to 13.0 ppm) is defined as Y, and the methine proton (-CH2C H The total integrated value (2.6 ppm to 3.0 ppm) of the peak (R1)CH2CH(R2)-) (here R1 and R2 are bonded to each other to form (-R1-R2-), -R1-R2- represents a -CO-O- structure) is X, and the total integrated value (2.6 ppm to 3.0 ppm) of the peak (R1)CH2CH(R2)-) derived from vinyl alcohol is X. H The total integrated value of the peak of (OH)-) (peak at 3.6 ppm to 4.0 ppm) is defined as W, and the side chain protons derived from vinyl acetate (-CH2CH(OCOC H 3) The integrated value of the peak of -) (1.9 ppm to 2.0 ppm) was defined as P, and the content (Z) (mol %) of the [acrylic acid-based monomer unit] relative to the [total monomer units of the vinyl alcohol-based block copolymer] was calculated by the following formula.
[0107] Note that, in the case of a lactone ring, one molecule of a lactone ring is generated by reacting one acrylic monomer unit with one adjacent vinyl alcohol monomer unit. In consideration of this, the coefficient of the denominator X is set to 2 and the coefficient of the numerator X is set to 1 in the following formula.
[0108] (Z) (mol%) = [acrylic acid monomer unit (molar content)] / [total monomer units (molar content) of vinyl alcohol block copolymer] × 100
[0109] =(X+Y) / (W+2X+Y+(P / 3))×100
[0110] The molar ratio (V) of lactone rings to the total of acrylic acid monomer units and lactone rings in a polymer obtained by heating the vinyl alcohol block copolymer in an acidic aqueous solution and then drying [lactone rings / total of acrylic acid monomer units and lactone rings] is calculated by the following formula using X and Y.
[0111] (V) = [lactone ring] / [total of acrylic monomer unit and lactone ring]
[0112] =X / (X+Y)
[0113] [Content (R) of acrylic acid monomer units in copolymer block (Bc) containing vinyl alcohol monomer units and acrylic acid monomer units]
[0114] The number average degree of polymerization DP of the vinyl alcohol block copolymer is used a , the number average degree of polymerization DP of the vinyl alcohol polymer block (Bb) bThe content (R) (mol %) of the acrylic acid-based monomer unit in the copolymer block (Bc) in the vinyl alcohol-based block copolymer relative to all monomer units is calculated by the following formula.
[0115] (R)(mol%)=(Z)×DP a / (DP a -DP b )
[0116] [Saponification degree]
[0117] The methine proton (-CH2C H The total integrated value (2.6 ppm to 3.0 ppm) of the peak (R1)CH2CH(R2)-) (here R1 and R2 are bonded to each other to form (-R1-R2-), -R1-R2- represents a -CO-O- structure) is X, and the total integrated value (2.6 ppm to 3.0 ppm) of the peak (R1)CH2CH(R2)-) derived from vinyl alcohol is X. H The total integrated value of the peak of (OH)-) (peak at 3.6 ppm to 4.0 ppm) is defined as W, and the side chain protons derived from vinyl acetate (-CH2CH(OCOC H 3) The integrated value of the peak of -) (1.9 ppm to 2.0 ppm) was defined as P, and the saponification degree (mol %) of the vinyl alcohol block copolymer was calculated by the following formula.
[0118] Saponification degree (mol%) = 100 - [(total number of moles of) vinyl acetate monomer unit] / [(total number of moles of) vinyl alcohol monomer unit for forming lactone ring + vinyl alcohol monomer unit + vinyl acetate monomer unit] × 100
[0119] =100-(P / 3) / (X+W+(P / 3))×100
[0120] [Crystallization melting temperature (Q)]
[0121] To 100 parts by mass of the vinyl alcohol block copolymer, 1860 parts by mass of methanol and 50 parts by mass of sodium hydroxide were added, and the remaining acetic acid groups were completely saponified (degree of saponification ≥ 99.9 mol%) by heating at 40°C for 2 hours. When the saponification is insufficient, sodium hydroxide is added to continue the reaction until the remaining acetic acid groups are completely saponified. Then, a phenolphthalein solution is added, and the mixture is washed with methanol until no alkaline reaction is observed in the washing liquid, and the sodium hydroxide and sodium acetate are removed. The washed polymer is dried at 120°C until the methanol disappears, thereby obtaining a vinyl alcohol block copolymer for measuring the crystalline melting temperature.
[0122] The crystal melting temperature of the above-mentioned vinyl alcohol block copolymer under nitrogen atmosphere was measured using a differential scanning calorimeter "DSC25" manufactured by TA Instruments. 3 mg of the vinyl alcohol block copolymer dried under reduced pressure at 90°C for 2 days was sealed in an aluminum container, placed in a differential scanning calorimeter, heated from 40°C to 250°C at a rate of 10°C per minute, and stored for 1 minute. The temperature was then lowered to -80°C at a rate of 10°C per minute and kept for 1 minute. The temperature was then raised to 250°C at a rate of 10°C per minute, and the temperature of the maximum point of the endothermic peak observed between 150°C and 250°C was taken as (Q)(°C).
[0123] [Dissolution rate in water]
[0124] The vinyl alcohol block copolymer was added to ion exchange water so as to have a concentration of 4% by mass, and dissolved by heating and stirring at 100° C. The solubility performance was evaluated according to the following criteria.
[0125] A: The copolymer was completely dissolved within 6 hours after the start of heating and stirring.
[0126] B: The copolymer was not completely dissolved within 6 hours after the start of heating and stirring.
[0127] [Viscosity stability of aqueous solution relative to pH]
[0128] The vinyl alcohol block copolymer was added to ion exchange water in a concentration of 4 mass %, heated and stirred at 100° C. to dissolve, and then the pH was adjusted to 2 or 12 using a hydrochloric acid aqueous solution or a sodium hydroxide aqueous solution, and then stirred at 20° C. for 1 hour. The viscosity stability of the aqueous solution relative to pH was evaluated by the following criteria. If the criteria was A, it can be said that the viscosity stability of the aqueous solution was high and good.
[0129] A: Comparison of the fluidity of aqueous solutions at pH 2 and pH 12 showed no significant difference in the viscosity of the aqueous solutions.
[0130] B: Comparison of the fluidity of aqueous solutions at pH 2 and pH 12 revealed significant differences in the viscosity of the aqueous solutions.
[0131] [Saturated moisture content]
[0132] An aqueous solution of a vinyl alcohol block copolymer with a concentration of 10% by mass was prepared, cast into a mold frame made of PET, and left to dry for one week in a room adjusted to 20°C and 21% RH. The obtained film was taken out of the mold frame, and the film thickness at the center was measured with a thickness gauge. The film with a film thickness of 100 μm was used as the evaluation object. After the obtained film was humidified at 20°C and 80% RH for one week, a part of the film was cut off, and the saturated moisture content [mass %] of the film was measured with a halogen moisture meter (set temperature 150°C).
[0133] [Mechanical properties]
[0134] The film used in the evaluation of the saturated moisture content was dried at 20°C and 80% RH for one week and cut into 10 mm × 800 mm pieces. Strength-elongation was measured using an autograph "AG-IS" manufactured by Shimadzu Corporation at a chuck distance of 50 mm and a tensile speed of 500 mm / min. The elastic modulus [kgf / mm2] at 20°C and 80% RH was determined. 2 ]. It should be noted that, regarding the measurement, each sample was measured 5 times, and the average value was calculated.
[0135] [Example 1]
[0136] 0.24 parts by mass of cobalt (II) acetylacetonate [Co(acac)2] and 0.86 parts by mass of V-70 [2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile)] as an initiator were added to a reactor equipped with a stirrer, a reflux condenser, and an initiator. The reactor was evacuated three times and then replaced with an inert gas by introducing nitrogen. 640 parts by mass of vinyl acetate (VAc) purified by single distillation was then added, and the reactor was immersed in a water bath and heated and stirred so that the internal temperature was 30°C. Sampling was performed appropriately, and the progress of polymerization was confirmed by its solid content concentration. When the conversion rate of vinyl acetate reached 19% by mass, 1.2 parts by mass of methyl acrylate (MA) were added. The number average molecular weight (Mn) of the polymer at a conversion rate of 19% by mass was 128,100. Then, appropriate samples were taken to confirm the progress of polymerization from the solid content concentration, and when the total conversion of vinyl acetate and methyl acrylate reached 22% by mass, 0.84 parts by mass of 1,1-diphenylethylene (1,1-DPEt) was added as a polymerization inhibitor. The induction period was 7 hours and the growth period was 4 hours.
[0137] After adding the polymerization inhibitor, the internal temperature was raised to 60°C, heated and stirred for 1 hour, 600 parts by weight of an aqueous solution of acetic acid (pH 2.0) with a concentration of 25% by mass was added thereto, stirred for 5 minutes, and then allowed to stand for 30 minutes to separate into two layers, and the water layer was removed. After being connected to a vacuum line, unreacted monomers were distilled off under reduced pressure at 30°C, methanol was added to dissolve the polymer, and the solution was added dropwise to deionized water to precipitate the vinyl ester block copolymer. The vinyl ester block copolymer was recovered by filtering, and dried in a vacuum dryer at 40°C for 24 hours to obtain a vinyl ester block copolymer. The details of the above polymerization process are shown in Table 1.
[0138] Then, 100 parts by mass of the obtained vinyl ester block copolymer and 334.2 parts by mass of dehydrated methanol were added to the same reactor as above and dissolved, and then heated in a water bath and heated with stirring until the internal temperature reached 40°C. 65.8 parts by mass of a methanol solution of sodium hydroxide (concentration 14% by mass, 9.2 parts by mass as sodium hydroxide) were added thereto. Saponification reaction was carried out at 40°C in the vinyl ester block copolymer solution with a concentration of 20% by mass prepared in this way. The resulting gel was crushed with a grinder and then placed at 40°C for 1 hour of saponification. 50.0 parts by mass of dehydrated methanol and 0.2 parts by mass of ion exchange water were added to the obtained saponified product, and heating was continued at 65°C for another hour. After that, acetic acid was added to adjust the pH to 5, and then filtered to obtain a solid, to which 500 parts by mass of methanol were added, and heated to reflux for 1 hour. After centrifugal dehydration, the obtained solid was dried in a vacuum dryer at 40° C. for 24 hours to obtain the target vinyl alcohol block copolymer (vinyl alcohol polymer block (Bb)-copolymer block (Bc) binary block copolymer). The details of the above saponification step are shown in Table 2.
[0139] The various physical properties of the obtained vinyl alcohol block copolymer were measured to evaluate the performance. The number average molecular weight (Mn a ) is 77200, the number average degree of polymerization (DP a ) is 1750, and the number average degree of polymerization (DP b ) is 1490, which is higher than (DP b / DP a ) is 0.851, and the molecular weight distribution (Mw a / Mn a ) is 1.40, and the saponification degree is 99.8 mol%. a / Mn a ) is obtained from the results of GPC measurement of the vinyl alcohol block copolymer. In addition, the content (Z) of acrylic acid monomer units is 0.9 mol%, the content (R) of acrylic acid monomer units in the "copolymer block (Bc) containing vinyl alcohol monomers and acrylic acid monomers" is 5.8 mol%, the crystalline melting temperature (Q) is 228.0°C, and the value of 2Z+Q is 230. The molar ratio (V) of lactone rings to the total of acrylic acid monomer units and lactone rings in the polymer obtained by heating the above-mentioned vinyl alcohol block copolymer in an acidic aqueous solution and then drying [lactone rings / total of acrylic acid monomer units and lactone rings] is 1.00. The evaluation of the dissolution rate in water is A, and the evaluation of the viscosity stability of the aqueous solution relative to pH is A. The saturated water content is 14.0% by mass, and the elastic modulus is 17.1 kgf / mm 2 The above results are summarized in Table 3.
[0140] [Example 2]
[0141] The polymerization of vinyl acetate was started in the same manner as in Example 1. Sampling was performed appropriately, and the progress of polymerization was confirmed by the solid content concentration. When the conversion rate of vinyl acetate reached 9% by mass, 16.0 parts by mass of methyl acrylate were added. The number average molecular weight (Mn) of the polymer at a conversion rate of 9% by mass was 60100. Then, sampling was performed appropriately, and the progress of polymerization was confirmed by the solid content concentration. When the total conversion rate of vinyl acetate and methyl acrylate reached 12% by mass, 0.50 parts by mass of para-benzoquinone was added as an inhibitor. The induction period was 7 hours, and the growth period was 2 hours. After adding the inhibitor, the same operation as in Example 1 was performed to obtain a vinyl ester block copolymer. The details of the above polymerization process are shown in Table 1.
[0142] Then, 100 parts by mass of the obtained vinyl ester block copolymer and 388.3 parts by mass of dehydrated methanol were added to the same reactor as above and dissolved, and then heated in a water bath and heated with stirring until the internal temperature reached 40°C. 11.3 parts by mass of a methanol solution of sodium hydroxide (concentration 14% by mass, 1.6 parts by mass as sodium hydroxide) were added thereto. A saponification reaction was carried out at 40°C in the vinyl ester block copolymer solution having a concentration of 20% by mass prepared in this way. The resulting gel was crushed with a grinder and then placed at 40°C for 1 hour of saponification. 50.0 parts by mass of dehydrated methanol and 3.1 parts by mass of ion exchange water were added to the obtained saponified product, and heating was continued at 40°C for another hour.
[0143] Thereafter, the target vinyl alcohol block copolymer (binary block copolymer of vinyl alcohol polymer block (Bb)-copolymer block (Bc)) was obtained by the same method as in Example 1. The details of the saponification step are shown in Table 2. In addition, the results of the measurement and evaluation of the obtained vinyl alcohol block copolymer are summarized in Table 3.
[0144] [Example 3]
[0145] Polymerization of vinyl acetate and methyl acrylate was started in the same manner as in Example 1 except that 2.4 parts by mass of methyl acrylate was added together with vinyl acetate. Sampling was performed appropriately, and the progress of polymerization was confirmed from the solid content concentration thereof. GPC measurement and 1 H-NMR determination, 1H-NMR confirmed that the methyl acrylate monomer was completely consumed when the total conversion rate of vinyl acetate and methyl acrylate was 5% [molar ratio (acrylate / vinyl ester) was less than 0.00001]. The number average molecular weight (Mn) at this time was 34500. Then, polymerization was carried out, and 2.4 parts by mass of methyl acrylate were added when the total conversion rate of vinyl acetate and methyl acrylate reached 14% by mass. The number average molecular weight (Mn) at the conversion rate of 14% by mass was 94500. Then, sampling was appropriately carried out, and the progress of polymerization was confirmed by its solid content concentration. When the total conversion rate of vinyl acetate and methyl acrylate reached 19% by mass, 0.84 parts by mass of 1,1-diphenylethylene was added as an inhibitor. The induction period was 7 hours and the growth period was 3 hours. After adding the inhibitor, the same operation as in Example 1 was carried out to obtain a vinyl ester block copolymer. The details of the above polymerization process are shown in Table 1.
[0146] Then, 100 parts by mass of the obtained vinyl ester block copolymer and 336.9 parts by mass of dehydrated methanol were added to the same reactor as above and dissolved, and then heated in a water bath and heated with stirring until the internal temperature reached 40°C. 63.1 parts by mass of a methanol solution of sodium hydroxide (concentration 14% by mass, 8.8 parts by mass as sodium hydroxide) were added thereto. A saponification reaction was carried out at 40°C in the vinyl ester block copolymer solution having a concentration of 20% by mass prepared in this way. The resulting gel was crushed with a grinder and then placed at 40°C for 1 hour for saponification. 50.0 parts by mass of dehydrated methanol and 1.0 parts by mass of ion exchange water were added to the obtained saponified product, and heating was continued at 65°C for another hour.
[0147] Thereafter, the target vinyl alcohol block copolymer (a ternary block copolymer of copolymer block (Bc)-vinyl alcohol polymer block (Bb)-copolymer block (Bc)) was obtained by the same method as in Example 1. The details of the saponification step are shown in Table 2. In addition, the results of the measurements and evaluations of the obtained vinyl alcohol block copolymer are summarized in Table 3.
[0148] [Example 4]
[0149] Into a reactor equipped with a stirrer, a reflux condenser, and an initiator addition port, 0.10 parts by mass of cobalt (II) acetylacetonate and 0.34 parts by mass of V-70 [2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile)] as an initiator were added, and the reactor was evacuated three times and then replaced with an inert gas by introducing nitrogen. Then, 640 parts by mass of vinyl acetate and 160 parts by mass of methyl acetate purified by single distillation were added, and the reactor was immersed in a water bath and heated and stirred so that the internal temperature was 30°C. Sampling was performed appropriately, and the progress of polymerization was confirmed by its solid content concentration. When the conversion rate of vinyl acetate reached 15% by mass, 6.4 parts by mass of methyl acrylate were added. The number average molecular weight (Mn) of the polymer at a conversion rate of 15% by mass was 257,100. Then, sampling was appropriately performed, and the progress of polymerization was confirmed by the solid content concentration. When the total conversion rate of vinyl acetate and methyl acrylate reached 20% by mass, 0.33 parts by mass of 1,1-diphenylethylene was added as a polymerization inhibitor. The induction period was 4 hours, and the growth period was 3 hours. After adding the polymerization inhibitor, the same operation as in Example 1 was performed to obtain a vinyl ester block copolymer. The details of the above polymerization process are shown in Table 1.
[0150] Then, 100 parts by mass of the obtained vinyl ester block copolymer and 396.8 parts by mass of dehydrated methanol were added to the same reactor as above and dissolved, and then heated in a water bath and heated with stirring until the internal temperature reached 40°C. 3.2 parts by mass of a methanol solution of sodium hydroxide (concentration 14% by mass, 0.4 parts by mass as sodium hydroxide) were added thereto. A saponification reaction was carried out at 40°C in the vinyl ester block copolymer solution having a concentration of 20% by mass prepared in this way. The resulting gel was crushed with a grinder and then placed at 40°C for 1 hour of saponification. 50.0 parts by mass of dehydrated methanol and 1.0 parts by mass of ion exchange water were added to the obtained saponified product, and heating was continued at 40°C for another hour.
[0151] Thereafter, the target vinyl alcohol block copolymer (binary block copolymer of vinyl alcohol polymer block (Bb)-copolymer block (Bc)) was obtained by the same method as in Example 1. The details of the saponification step are shown in Table 2. In addition, the results of the measurement and evaluation of the obtained vinyl alcohol block copolymer are summarized in Table 3.
[0152] [Example 5]
[0153] The polymerization of vinyl acetate was started in the same manner as in Example 1 except that 0.96 parts by mass of cobalt (II) acetylacetonate and 3.44 parts by mass of V-70 [2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile)] as an initiator were added. Sampling was performed appropriately, and the progress of polymerization was confirmed by its solid content concentration. When the conversion rate of vinyl acetate reached 20% by mass and 24% by mass, 1.6 parts by mass of methyl acrylate were added respectively. The number average molecular weight (Mn) of the polymer at a conversion rate of 20% by mass was 34,400. Then, sampling was performed appropriately, and the progress of polymerization was confirmed by its solid content concentration. When the combined conversion rate of vinyl acetate and methyl acrylate reached 28% by mass, 3.35 parts by mass of 1,1-diphenylethylene was added as an inhibitor. The induction period was 12 hours, and the growth period was 3 hours. After adding the inhibitor, the same operation as in Example 1 was performed to obtain a vinyl ester block copolymer. The details of the above polymerization process are shown in Table 1.
[0154] Then, 100 parts by mass of the obtained vinyl ester block copolymer and 335.0 parts by mass of dehydrated methanol were added to the same reactor as above and dissolved, and then heated in a water bath and heated with stirring until the internal temperature reached 40°C. 65.0 parts by mass of a methanol solution of sodium hydroxide (concentration 14% by mass, 9.1 parts by mass as sodium hydroxide) were added thereto. A saponification reaction was carried out at 40°C in the vinyl ester block copolymer solution having a concentration of 20% by mass prepared in this way. The resulting gel was crushed with a grinder and then placed at 40°C for 1 hour of saponification. 50.0 parts by mass of dehydrated methanol and 0.4 parts by mass of ion exchange water were added to the obtained saponified product, and heating was continued at 65°C for another hour.
[0155] Thereafter, the target vinyl alcohol block copolymer (binary block copolymer of vinyl alcohol polymer block (Bb)-copolymer block (Bc): it should be noted that methyl acrylate was added in two portions when the copolymer block (Bc) was prepared) was obtained by the same method as in Example 1. The details of the saponification step are shown in Table 2. In addition, the results of the measurement and evaluation of the obtained vinyl alcohol block copolymer are summarized in Table 3.
[0156] [Example 6]
[0157] The target vinyl alcohol block copolymer was obtained by the same method as in Example 1 except that the saponification was performed at 40°C for 1 hour and dehydrated methanol and ion exchange water were not added to the obtained saponified product. The details of the saponification step are shown in Table 2. In addition, the results of measurement and evaluation of the obtained vinyl alcohol block copolymer are summarized in Table 3.
[0158] [Example 7]
[0159] The polymerization of vinyl acetate is started in the same manner as in Example 1. Sampling is performed appropriately, and the progress of polymerization is confirmed by its solid content concentration. When the conversion rate of vinyl acetate reaches 19% by mass, 49.0 parts by mass of methyl acrylate are added. The number average molecular weight (Mn) of the polymer at a conversion rate of 19% by mass is 128100. Then, sampling is performed appropriately, and the progress of polymerization is confirmed by its solid content concentration. When the combined conversion rate of vinyl acetate and methyl acrylate reaches 30% by mass, 0.84 parts by mass of 1,1-diphenylethylene is added as an inhibitor. The induction period is 7 hours, and the growth period is 4 hours. After adding the inhibitor, the same operation as in Example 1 is performed to obtain a vinyl ester block copolymer. The details of the above polymerization process are shown in Table 1.
[0160] Then, 100 parts by mass of the obtained vinyl ester block copolymer and 334.2 parts by mass of dehydrated methanol were added to the same reactor as above and dissolved, and then heated in a water bath and heated with stirring until the internal temperature reached 40°C. 65.8 parts by mass of a methanol solution of sodium hydroxide (concentration 14% by mass, 9.2 parts by mass as sodium hydroxide) were added thereto. A saponification reaction was carried out at 40°C in the vinyl ester block copolymer solution having a concentration of 20% by mass prepared in this way. The resulting gel was crushed with a grinder and then placed at 40°C for 1 hour for saponification. 50.0 parts by mass of dehydrated methanol and 7.7 parts by mass of ion exchange water were added to the obtained saponified product, and heating was continued at 65°C for another hour.
[0161] Thereafter, the target vinyl alcohol block copolymer (binary block copolymer of vinyl alcohol polymer block (Bb)-copolymer block (Bc)) was obtained by the same method as in Example 1. The details of the saponification step are shown in Table 2. In addition, the results of the measurement and evaluation of the obtained vinyl alcohol block copolymer are summarized in Table 3.
[0162] [Comparative Example 1]
[0163] The polymerization of vinyl acetate is started in the same manner as in Example 1. Sampling is performed appropriately, and the progress of polymerization is confirmed by its solid content concentration. When the conversion rate of vinyl acetate reaches 13% by mass, 80.0 parts by mass of methyl acrylate are added. The number average molecular weight (Mn) of the polymer at a conversion rate of 13% by mass is 85,800. Then, sampling is performed appropriately, and the progress of polymerization is confirmed by its solid content concentration. When the combined conversion rate of vinyl acetate and methyl acrylate reaches 30% by mass, 0.84 parts by mass of 1,1-diphenylethylene is added as an inhibitor. The induction period is 7 hours, and the growth period is 4 hours. After adding the inhibitor, the same operation as in Example 1 is performed to obtain a vinyl ester block copolymer. The details of the above polymerization process are shown in Table 1.
[0164] Then, 100 parts by mass of the obtained vinyl ester block copolymer and 358.1 parts by mass of dehydrated methanol were added to the same reactor as above and dissolved, and then heated in a water bath and heated with stirring until the internal temperature reached 40°C. 41.9 parts by mass of a methanol solution of sodium hydroxide (concentration 14% by mass, 5.9 parts by mass as sodium hydroxide) were added thereto. A saponification reaction was carried out at 40°C in the vinyl ester block copolymer solution having a concentration of 20% by mass prepared in this way. The resulting gel was crushed with a grinder and then placed at 40°C for 1 hour of saponification. 50.0 parts by mass of dehydrated methanol and 7.7 parts by mass of ion exchange water were added to the obtained saponified product, and heating was continued at 65°C for another hour.
[0165] Thereafter, the target vinyl alcohol block copolymer (binary block copolymer of vinyl alcohol polymer block (Bb)-copolymer block (Bc)) was obtained by the same method as in Example 1. The details of the saponification step are shown in Table 2. In addition, the results of the measurement and evaluation of the obtained vinyl alcohol block copolymer are summarized in Table 3.
[0166] [Comparative Example 2]
[0167] The target vinyl alcohol block copolymer was obtained by the same method as in Comparative Example 1 except that the saponification was performed at 40°C for 1 hour and dehydrated methanol and ion exchange water were not added to the obtained saponified product. The details of the saponification step are shown in Table 2. In addition, the results of measurement and evaluation of the obtained vinyl alcohol block copolymer are summarized in Table 3.
[0168] [Comparative Example 3]
[0169] To a reactor equipped with a stirrer, a reflux condenser, an argon inlet, an initiator addition port, and a feed pump, 640 parts by mass of vinyl acetate, 1.1 parts by mass of methyl acrylate, and 250 parts by mass of methanol were added, and the reactor was replaced with an inert gas for 30 minutes while nitrogen was blown in. The temperature of the reactor was started by heating a water bath, and 0.15 parts by mass of azobisisobutyronitrile (AIBN) was added as an initiator when the internal temperature reached 60°C to start polymerization. While feeding a 40% by mass methanol solution of methyl acrylate over time, polymerization was carried out, and sampling was performed appropriately. The progress of polymerization was confirmed by its solid content concentration. When the total conversion rate of vinyl acetate and methyl acrylate reached 35% by mass, 0.10 parts by mass of para-benzoquinone was added to terminate the polymerization. The total feed amount of methyl acrylate at this moment was equivalent to 11.4 parts by mass. After adding the polymerization inhibitor, the same operation as in Example 1 was performed to obtain a vinyl ester random copolymer. The details of the above polymerization process are shown in Table 1.
[0170] Then, 100 parts by mass of the obtained random copolymer of vinyl esters and 336.9 parts by mass of dehydrated methanol were added to the same reactor as in Example 1 and dissolved, and then heated in a water bath and heated with stirring until the internal temperature reached 40°C. 63.1 parts by mass of a methanol solution of sodium hydroxide (concentration 14% by mass, 8.8 parts by mass as sodium hydroxide) were added thereto. A saponification reaction was carried out at 40°C in the random copolymer solution of vinyl esters having a concentration of 20% by mass prepared in this way. The resulting gel was crushed with a grinder and then placed at 40°C for 1 hour for saponification. 50.0 parts by mass of dehydrated methanol and 1.0 parts by mass of ion exchange water were added to the obtained saponified product, and heating was continued at 65°C for another hour. Thereafter, the target random copolymer of vinyl alcohol was obtained by the same method as in Example 1. The details of the saponification process are shown in Table 2. In addition, the results of the measurement and evaluation of the obtained random copolymer of vinyl alcohol are summarized in Table 3.
[0171] [Comparative Example 4]
[0172] In a reactor equipped with a stirrer, a reflux condenser, and an initiator addition port, 1.56 parts by mass of tetramesitylporphyrin cobalt (II) [Co(TMP)] and 0.91 parts by mass of azobisisobutyronitrile (AIBN) as an initiator were added, and the reactor was evacuated three times and then replaced with an inert gas by introducing nitrogen. After that, 160.0 parts by mass of methyl acrylate purified by single distillation and 480 parts by mass of toluene were added, and the reactor was immersed in a water bath, heated and stirred to an internal temperature of 60°C. Sampling was performed appropriately, and the progress of polymerization was confirmed by its solid content concentration. When the conversion rate of methyl acrylate reached 18%, the polymerization was terminated by cooling to 30°C. The number average molecular weight (Mn) of the polymer at a conversion rate of 18% was 15,500. Connect to a vacuum line, and distill off the residual methyl acrylate and toluene under reduced pressure at 30°C. After adding 640 parts by mass of vinyl acetate, the internal temperature was heated and stirred to 60°C. Sampling was appropriately performed, and the progress of polymerization was confirmed by the solid content concentration. When the conversion rate of vinyl acetate reached 22% by mass, 1.68 parts by mass of 1,1-diphenylethylene was added as a polymerization inhibitor. The induction period was 5 hours, and the growth period was 4 hours. After adding the polymerization inhibitor, the same operation as in Example 1 was performed to obtain a vinyl ester block copolymer. The details of the above polymerization process are shown in Table 1.
[0173] Then, 100 parts by mass of the obtained vinyl ester block copolymer and 344.9 parts by mass of dehydrated methanol were added to the same reactor as above and dissolved, and then heated in a water bath and heated with stirring until the internal temperature reached 40°C. 55.1 parts by mass of a methanol solution of sodium hydroxide (concentration 14% by mass, 7.7 parts by mass as sodium hydroxide) were added thereto. A saponification reaction was carried out at 40°C in the vinyl ester block copolymer solution having a concentration of 20% by mass prepared in this way. The resulting gel was crushed with a grinder and then placed at 40°C for 1 hour for saponification. 50.0 parts by mass of dehydrated methanol and 3.6 parts by mass of ion exchange water were added to the obtained saponified product, and heating was continued at 65°C for another hour.
[0174] Thereafter, the target vinyl alcohol block copolymer (binary block copolymer of methyl acrylate polymer block-vinyl alcohol polymer block (Bb)) was obtained by the same method as in Example 1. The details of the saponification step are shown in Table 2. In addition, the results of measurement and evaluation of the obtained vinyl alcohol block copolymer are summarized in Table 3.
[0175]
[0176]
[0177]
[0178] The block copolymers of Examples 1 to 7 were good in terms of dissolution rate in water (water solubility), stability of viscosity of aqueous solution with respect to pH (pH stability), and mechanical properties (elastic modulus).
[0179] The block copolymer of Example 4 has a low saponification degree, so Mn a The DP of the block copolymer of Example 5 is relatively large, but the mechanical properties are lower than those of Example 1. b The mechanical properties of the block copolymer of Example 6 are lower than those of Example 1 because the (V) value of the block copolymer of Example 7 is smaller than that of Examples 1 to 6. In Example 1, a treatment of adding dehydrated methanol and ion exchange water to the saponified product was performed, but in Example 6, this treatment was not performed, so the acrylate monomer units were not converted into acrylic acid units and remained. As a result, the mechanical properties of the block copolymer of Example 6 are lower than those of Example 1. In addition, the (V) value of the block copolymer of Example 7 is smaller, so the pH stability of the aqueous solution is lower than that of Examples 1 to 6.
[0180] The block copolymer of Comparative Example 1 has a large value of content (Z), poor pH stability and mechanical properties. The block copolymer of Comparative Example 2 has a large value of content (Z), and because it does not add dehydrated methanol and ion exchange water to the saponified product, it contains more acrylate monomer units, so it has poor water solubility. The copolymer of Comparative Example 3 is not a block copolymer but a random copolymer, and the value of molecular weight distribution is also large, and the mechanical properties are poor. The block copolymer of Comparative Example 4 contains a methyl acrylate monomer block, but does not contain a copolymer block (Bc), and has poor pH stability.
Claims
1. A vinyl alcohol block copolymer, which is a block copolymer consisting of a vinyl alcohol polymer block (Bb) and a copolymer block (Bc) containing a vinyl alcohol monomer unit and an acrylic acid monomer unit, wherein: The content (Z) of the acrylic acid monomer unit relative to all monomer units is 0.05 to 20.0 mol%. The saponification degree is 80 to 99.99 mol%. The number average molecular weight (Mn) of the block copolymer a ) is 20000~440000, Molecular weight distribution (Mw a / Mn a ) is 1.05~1.95, The number average degree of polymerization (DP b ) relative to the number average degree of polymerization (DP) of the block copolymer a ) ratio (DP b / DP a ) is 0.010~0.
999.
2. The block copolymer according to claim 1, wherein The number average degree of polymerization (DP b ) is 450 to 5000.
3. The block copolymer according to claim 1 or 2, wherein The content (R) of the acrylic monomer units in the copolymer block (Bc) is 0.1 to 50.0 mol % relative to all monomer units.
4. The block copolymer according to claim 1 or 2, wherein The content (Z) [mol %] of the acrylic monomer unit and the crystalline melting temperature (Q) [° C.] of the polymer obtained by re-saponifying the block copolymer to a saponification degree of 99 mol % or more satisfy the following formula (1): 2Z+Q≥225 (1).
5. The block copolymer according to claim 1 or 2, wherein The molar ratio (V) of lactone rings to the total of acrylic acid monomer units and lactone rings in a polymer obtained by heat-treating the block copolymer in an acidic aqueous solution and then drying [lactone rings / total of acrylic acid monomer units and lactone rings] is 0.70 or more.
6. The method for producing a block copolymer according to any one of claims 1 to 5, comprising: A polymerization step, wherein In the presence of a free radical initiator and an organic cobalt complex, vinyl ester is polymerized and vinyl ester and acrylic ester are copolymerized by controlled free radical polymerization to obtain a vinyl ester block copolymer consisting of a vinyl ester polymer block (B-b1) and a copolymer block (B-c1) containing vinyl ester monomer units and acrylic ester monomer units; and A saponification step of saponifying the vinyl ester block copolymer obtained in the polymerization step to obtain a vinyl alcohol block copolymer composed of a vinyl alcohol polymer block (Bb) and a copolymer block (Bc) containing a vinyl alcohol monomer unit and an acrylic acid monomer unit.
7. The method for producing a vinyl alcohol block copolymer according to claim 6, wherein: The acrylic acid ester is methyl acrylate.
